Investigation of technological trends in shading devices through patent analysis. Issue 6 (17th August 2016) - Perng, Yeng-Horng; Huang, Yu-Ying
Abstract: In recent years, the issues of energy use reduction and sustainable development have garnered considerable interest. This study has conducted a patent search using United States Patent and Trademarks Office (USPTO) data to investigate technological trends in sustainable development, using shading devices for buildings as an example, because they have the potential to save energy by effectively preventing heat from coming indoors, and lowering the indoor heat load. The purpose of this study was to explore the status of shading devices and analyze patent activity, major assignees, assignee countries, core technology fields, patent citations, potential competitors of patent assignees, and developmental path based on patent analysis using a database that spanned the years from 1974 to 2011. The results provide a clear picture of, and evidence for, the pattern of shading device technology; they suggest that automatic sensing shading devices are the focus of current technological developments, thus saving time and costs in future research development.